2018
DOI: 10.1111/nmo.13310
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative high‐resolution mapping of slow wave propagation in the human jejunum: Feasibility and initial results

Abstract: This study introduces HR mapping of human intestinal slow waves, and provides first descriptions of intestinal pacemaker sites and velocity anisotropy. Future translation to other intestinal regions, disease states, and postsurgical dysmotility holds potential for improving the basic and clinical understanding of small intestine pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
(141 reference statements)
1
28
0
Order By: Relevance
“…However, in the rabbits the ileal frequency was found to be similar to that of pigs (10.5 cpm in rabbits vs 11.6 cpm in pigs). In comparison, the slow‐wave frequency in the proximal jejunum was higher in rabbits than in humans (9.8 ± 0.4 vs 16.8 ± 1.1 cpm) …”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…However, in the rabbits the ileal frequency was found to be similar to that of pigs (10.5 cpm in rabbits vs 11.6 cpm in pigs). In comparison, the slow‐wave frequency in the proximal jejunum was higher in rabbits than in humans (9.8 ± 0.4 vs 16.8 ± 1.1 cpm) …”
Section: Discussionmentioning
confidence: 83%
“…The term pacemaker was used to describe the origin of slow‐wave activity in the duodenum recorded extracellularly. To date, HR mapping has been applied to several studies investigating the slow‐wave characteristics in the small intestine of animals and humans . It has shown that multiple pacemakers (ie, sites of slow‐wave initiation) exist along the intestine and the location of these pacemakers can move over .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations